2021
DOI: 10.1186/s12981-021-00387-3
|View full text |Cite
|
Sign up to set email alerts
|

Treatment outcomes among adults with HIV/non-communicable disease multimorbidity attending integrated care clubs in Cape Town, South Africa

Abstract: Background The growing burden of the HIV and non-communicable disease (NCD) syndemic in Sub- Saharan Africa has necessitated introduction of integrated models of care in order to leverage existing HIV care infrastructure for NCDs. However, there is paucity of literature on treatment outcomes for multimorbid patients attending integrated care. We describe 12-month treatment outcomes among multimorbid patients attending integrated antiretroviral treatment (ART) and NCD clubs in Cape Town, South A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 33 publications
(37 reference statements)
0
14
0
Order By: Relevance
“…The integration of hypertension and other non-communicable diseases services into the well-established health services was explored in 18% (7/39) of the studies in 6 different countries [35, 43, 45, 46, 49, 60, 61]. The most frequent form of cross-integration was the provision of non-communicable diseases services in the Human Immunodeficiency Virus (HIV) and Sexually Transmitted Diseases clinics and the use of existing patient follow-up mechanisms in managing non-communicable diseases.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The integration of hypertension and other non-communicable diseases services into the well-established health services was explored in 18% (7/39) of the studies in 6 different countries [35, 43, 45, 46, 49, 60, 61]. The most frequent form of cross-integration was the provision of non-communicable diseases services in the Human Immunodeficiency Virus (HIV) and Sexually Transmitted Diseases clinics and the use of existing patient follow-up mechanisms in managing non-communicable diseases.…”
Section: Resultsmentioning
confidence: 99%
“…Predominantly, the cross-integration of services has shown significant improvements in hypertension control. A cohort of patients in South Africa increased in controlled BP from 43% before integration of services to 49% one year after integration [45]. Another cohort of patients in Uganda and Tanzania had a 10% decline in the risk of uncontrolled BP [43].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A new theme that emerged from 11 of the studies was that of improving patient access to chronic disease care. Barriers to patient access were long distances to travel to clinic, a lack of public transport, low vehicle ownership,34 35 45 a loss of income resulting from time away from the workplace, very long waiting times, and separate appointments for those with more than one chronic disease 35 36 41 42 46. Several studies identified the need for decentralisation of chronic care to primary care level to reduce travel time and costs 32 34 45 47.…”
Section: Resultsmentioning
confidence: 99%